Preparation of Dendrobium officinale flower oligosaccharides and the value-added effects on three types of probiotics - ZHANG, Zhenlin; BAO, Xianxiang; LIU, Ziwei; HOU, Dandan; WANG, Mengru (Food Science and Technology, 2023)
The present study prepared Dendrobium officinale flower oligosaccharides and investigated their added value in vitro. The crude oligosaccharides obtained by water extraction and alcohol precipitation were purified by ultrafiltration, and the value-added effects of different concentrations of D. officinale flower oligosaccharides on Saccharomycetes, Lactobacillus bulgaricus, and Streptococcus thermophilus were examined. The in vitro growth kinetic models for the three types of probiotics were established according to the logistic equation. Our results showed that a concentration of 8 g/L D. officinale flower oligosaccharides was most suitable for promoting the growth of the three types of probiotics, and the growth rates were significantly improved compared to the control group. Nonlinear fitting was performed for the in vitro growth kinetic models of the three bacteria according to the logistic equation, and the degrees of fit reached 0.9895, 0.9899, and 0.99, respectively, indicating a good fit. These kinetic models suitably depicted the in vitro growth processes of the three bacteria. D. officinale flower oligosaccharides promote the growth of Saccharomycetes, L. bulgaricus and S. thermophilus and improve the physiological activities of these microorganisms. This study provides a theoretical basis for the application of D. officinale flower oligosaccharides in the development of probiotic products.